Comparison of tide model outputs for the northern region of the Antarctic Peninsula using satellite altimeters and tide gauge data - Oreiro, Fernando Ariel (2014)
This study compares the common harmonic constants of the O1, K1, P1, Q1, M2, S2, N2, and K2 tidal constituents from eight global and four regional tide models with harmonic constants from satellite altimeter and tide gauge data for the northern region of the Antarctic Peninsula (58Se66S, 53We66W). To obtain a more representative comparison, the study area was divided into three zones with different physical characteristics but similar maximum tidal amplitude variations: Zone I (north of 62S), Zone II (south of 62S and west of the Antarctic Peninsula), and Zone III (between 62S and 64.3S, and east of 58.5W). Root sum square (RSS) values are less than or equal to 3.0, 4.2, and 8.4 cm for zones I, II, and III, respectively. No single model shows superior performance in all zones. Because there are insufficient satellite altimetry observations in the vicinity of Matienzo Base (64.9761S, 60.0683W), this station was analyzed separately and presents the greatest values of both root mean square misfit and RSS. The maximum, minimum, and average amplitude values of the constituents that follow in importance after the eight common tidal constituents, and which have amplitudes greater than 1 cm, are also analyzed.